Failure to Upregulate the RNA Binding Protein ZBP After Injury Leads to Impaired Regeneration in a Rodent Model of Diabetic Peripheral Neuropathy - Jones, James I.; Costa, Christopher J.; Cooney, Caitlin; Goldberg, David C.; Ponticiello, Matthew; Cohen, Melanie W.; Mellado, Wilfredo; Ma, Thong C.; Willis, Dianna E. (Frontiers in Molecular Neuroscience, 2021)
Most diabetes patients eventually suffer from peripheral nerve degeneration. Unfortunately, there is no treatment for the condition and its mechanisms are not well understood. There is, however, an emerging consensus that the inability of peripheral nerves to regenerate normally after injury contributes to the pathophysiology. We have previously shown that regeneration of peripheral axons requires local axonal translation of a pool of axonal mRNAs and that the levels and members of this axonal mRNA pool are altered in response to injury. Here, we show that following sciatic nerve injury in a streptozotocin rodent model of type I diabetes, this mobilization of RNAs into the injured axons is attenuated and correlates with decreased axonal regeneration. This failure of axonal RNA localization results from decreased levels of the RNA binding protein ZBP1. Over-expression of ZBP1 rescues the in vitro growth defect in injured dorsal root ganglion neurons from diabetic rodents. These results provide evidence that decreased neuronal responsiveness to injury in diabetes is due to a decreased ability to alter the pool of axonal mRNAs available for local translation, and may open new therapeutic opportunities for diabetic peripheral neuropathy.